Notes on the snake eel neenchelys buitendijki(Ophichthidae: Myrophinae), a new record for Malaysia - Ho, Hsuan-Ching; Teoh, Hong-Wooi; Chong, Ving-Ching (Universiti Kebangsaan Malaysia, 2012)
Neenchelys buitendijkiWeber and de Beaufort, 1916 from Malaysia is reported for the first time. Five specimens collected from Matang, Peninsular Malaysia, represent the third record in the Indo-western Pacific region. A detailed description is provided to document the species into the fish fauna of Malaysia.